New magnetic chelating sorbent for chromium speciation by magnetic solid phase extraction on-line with inductively coupled plasma optical emission spectrometry - Morales-Benítez, Irene; Montoro-Leal, Pablo; García-Mesa, Juan Carlos; López-Guerrero, María del Mar; Vereda-Alonso, Elisa Isabel (Elsevier, 2023)
A novel sorbent material employing magnetic nanoparticles (MNPs) coupled to graphene oxide (GO) functionalized with 4-aminobenzenesulfonic acid (M@GO-ABS) has been synthesized and applied to develop an inexpensive and automatic method for Cr(III) and Cr(VI) speciation in environmental samples; the developed method combines inductively coupled plasma optical emission spectrometry (ICP-OES) with on-line magnetic solid phase extraction (MSPE). Two magnetic-knotted reactors containing M@GO-ABS were installed in the eight-port injection valve of a flow injection (FI) manifold. Two different eluents were used, one for Cr(VI) (the most toxic chromium species) and one for total Cr concentration. Cr(III) concentration was calculated by the difference between Cr(VI) concentration and total Cr concentration. The optimized method presented detection limits (LOD, peak height) of 0.1 μg L
Keywords: Sólidos -- Propiedades magnéticas; Chromium speciation; Magnetic solid phase extraction; Inductively coupled plasma optical emission spectrometry; Environmental water samples